2008
DOI: 10.1021/bi8016747
|View full text |Cite
|
Sign up to set email alerts
|

Differential Potencies of Naturally Occurring Regioisomers of Nitrolinoleic Acid in PPARγ Activation

Abstract: Previous studies demonstrated that the naturally occurring electrophile and PPARgamma ligand, nitrolinoleic acid (NO(2)-LA), exists as a mixture of four regioisomers [Alexander, R. L., et al. (2006) Biochemistry 45, 7889-7896]. We hypothesized that these alternative isomers have distinct bioactivities; therefore, to determine if the regioisomers are quantitatively or qualitatively different with respect to PPARgamma activation, NO(2)-LA was separated into three fractions which were identified by NMR (13-NO(2)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 20 publications
6
36
0
Order By: Relevance
“…NO 2 -LA positional isomers have been previously described and confirmed by NMR [4, 32]. The CID fragmentation of 9-NO 2 -LA resulted in the formation of three main product ions containing structural information with m/z values of 168.1, 210.1, and 224.1 (Figure 2A).…”
Section: Resultssupporting
confidence: 59%
“…NO 2 -LA positional isomers have been previously described and confirmed by NMR [4, 32]. The CID fragmentation of 9-NO 2 -LA resulted in the formation of three main product ions containing structural information with m/z values of 168.1, 210.1, and 224.1 (Figure 2A).…”
Section: Resultssupporting
confidence: 59%
“…NO 2 -FAs and keto-fatty acid derivatives have high binding affinities for all three PPAR isotypes, with PPARγ the most robustly-activated receptor (followed by α and then δ) [31, 32•]. Reporter cell transactivation studies revealed that different regioisomers of NO 2 -FA behave as partial agonists [33•]. Receptor-ligand-binding analysis indicates that NO 2 -FA covalently react with the ligand binding domain Cys285 residue of PPARγ in both biochemical reaction systems and cells.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods are nonregiospecific, producing a mixture of positional isomers of NO 2 -LA with nitration at the 9-, 10-, 12-, and 13-positions ( 4–7 ). Studies that isolate and compare individual isomers, 21 synthesize regiospecific isomers 22 ( 5 and analogs 23 ), and characterize the degradation manifolds of particular isomers 24 ( 4 ) have been reported. These initial reports focused on understanding the nitration of LA because of its natural abundance and the presence of a reactive bisallylic methylene that favors hydrogen abstraction reactions.…”
Section: Introductionmentioning
confidence: 99%